Pengaruh Konseling Kelompok Teknik Cognitive Restructuring Terhadap Self Efficacy di Era Pembelajaran Daring Pada Siswa MTs Negeri 2 Medan - Novia Nita; Abdul Murad (Medan State University, 2022)
This study aims to determine the effect of group counseling with cognitive restructuring technique on self-efficacy in the era of online learning students of MTs Negeri 2 Medan. The method used in this research is quantitative method. This type of research is a quasi-experimental with a pretest-posttest group design. The subjects in this study were 8 students of class VIII-1 who had low self-efficacy scores. The research data were collected using a student self-efficacy questionnaire in the era of online learning, amounting to 47 statement items that had been valid and reliable. Questionnaires were given before and after the implementation of group counseling service. Data were analyzed using the Wilcoxon test to see if there was a significant effect of group counseling with cognitive restructuring technique on student self-efficacy in the era of online learning. This can be obtained from the Wilcoxon test which shows that the Wilcoxon level test is obtained. Jcount = 6 while Jtable = 4. From the critical value table J for the Wilcoxon-marked cascade test for n = 8, α = 0.05 according to the criteria for acceptance and rejection of the hypothesis, the hypothesis is accepted if Jcount> Jtabel where 6> 4, from this calculation It can be seen that the treatment in the experimental group means that the hypothesis is accepted. This shows that there is an effect of group counseling with cognitive restructuring technique on self-efficacy in the era of online learning students of MTs Negeri 2 Medan.